Double trouble in Walla Walla - Clements, Andrew, 1949-2019- (Millbrook Press, 1997)
It's an ordinary morning in Walla Walla until Lulu, her teacher, the school nurse, and the principal are all infected by a word warp which makes them reduplicate everything they say.